Shiloh : a biblical city in tradition and history - Schley, Donald G. (Sheffield, England : JSOT Press, 1989)
This work is the first comprehensive treatment of the biblical traditions pertaining to the Israelite sanctuary at Shiloh. A survey of previous research puts the current discussion of Shiloh into historical context and exposes the real issues behind the often bitter debate over Shiloh's supposed destruction during the Philistine wars and its traditional status as the first 'central' shrine.
Abbreviations; Preface; Chapter 1 SHILOH IN NINETEENTH-CENTURY OLD TESTAMENT CRITICISM: FROM DE WETTE TO THE RISE OF THE NEW DOCUMENTARY HYPOTHESIS; Chapter 2 THE WELLHAUSIAN REVOLUTION AND ITS CRITICS; Chapter 3 THE DISCUSSION OF SHILOH IN THE TWENTIETH CENTURY; Chapter 4 SHILOH IN THE BOOK OF JOSHUA; Chapter 5 SHILOH IN THE BOOK OF JUDGES; Chapter 6 SHILOH IN THE BOOKS OF SAMUEL; Chapter 7 SHILOH IN THE LATER HISTORICAL BOOKS, THE PSALMS, AND JEREMIAH; Chapter 8 THE TRADITIONS AND HISTORY OF BIBLICAL SHILOH; Appendix; Notes; Bibliography; Index of Biblical References.
Includes bibliographical references and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Critique, interprétation, etc; Bible; Bible. -- Critique, interprétation, etc; Documentary hypothesis (Pentateuchal criticism); Shiloh (Extinct city) -- History; West Bank -- Antiquities; Shiloh (Extinct city); Shiloh (Extinct city) -- Biblical teaching; Shiloh (Extinct city); Silo (Ville ancienne); Silo (Ville ancienne) -- Enseignement biblique; Théorie documentaire (Critique du Pentateuque); Silo (Ville ancienne) -- Histoire; Cisjordanie -- Antiquités.; RELIGION -- Judaism -- Sacred Writings; RELIGION -- Biblical Studies -- Old Testament; Biblical teaching; Antiquities; Documentary hypothesis (Pentateuchal criticism); West Bank; West Bank -- Shiloh (Extinct city); Silo (ville ancienne); Palestine, ancient period. -- Historical sources: Bible -- O.T; Criticism, interpretation, etc; History